A Basis for Modelling Creep and Stress Relaxation Behaviour of Geogrids. Issue 6 (1998) - Sawicki, A.
Abstract : Based on the test data published in 1997 by Leshchinsky et al., analytical models of the creep and stress relaxation of some geogrids are presented. It is shown that in the case of Geogrid C2 (high density polyethylene) a standard rheological model describes the experimental data in the low stress level range. In other cases, new rheological models can be developed, such as the new model proposed for Geogrid A1 (polyester). The models are defined by differential constitutive equations whose solutions are presented for creep at constant stress and stress relaxation at constant strain. Model parameters are also determined.